الأداء المؤسسي للأكاديمية المهنية بمصر في ضوء بطاقة الأداء المتوازن "BSC": دراسة تقويمية - جاد الله، باسم سليمان صالح (جامعة القاهرة - كلية الدراسات العليا للتربية, 2020)
هدف البحث إلى وضع تصور مقترح لتطوير الأداء المؤسسي للأكاديمية المهنية للمعلمين في ضوء بطاقة الأداء المتوازن، وتم عرض الإطار المفاهيمي والفكري للأكاديمية المهنية للمعلمين، وبطاقة الأداء المتوازن، واستخدم الباحث المنهج الوصفي لمناسبته لموضوع البحث. وطبق الباحث استبيان على السادة المسؤولين بالأكاديمية المهنية بالمعلم بمحافظات أسيوط، وسوهاج، والقاهرة، وتوصل البحث إلى أن مجالات بطاقة الأداء المتوازن والمتمثلة في التعليم والنمو في الأكاديمية المهنية للمعلم، والعمليات التشغيلية الداخلية في الأكاديمية المهنية للمعلم، والمستفيدين من الأكاديمية المهنية للمعلم، والجوانب المالية في الأكاديمية المهنية للمعلم جاءت بدرجة تحقق متوسطة من وجهة نظر أفراد العينة. مما دعى الباحث إلى وضع تصور مقترح لتطوير الأداء المؤسسي للأكاديمية المهنية للمعلمين في ضوء إطار بطاقة الأداء المتوازن، وتضمنت الخطوات الإجراءات التنفيذية للتصور المقترح ما يلى: التخطيط لتطبيق بطاقة الأداء المتوازن، والتهيئة لتطبيق بطاقة الأداء المتوازن، وجمع البيانات عن المؤسسة بالأكاديمية المهنية للمعلم، وتحديد المجالات الاستراتيجية لتطبيق بطاقة الأداء المتوازن، ورسم وتطوير المجالات الرئيسية للأكاديمية المهنية للمعلم، وتحديد عوامل النجاح الحرجة، وإعداد التقرير الأولي للبطاقة، والمتابعة وتقويم الأداء، وكل خطوة من تلك الخطوات لها مجموعة من آليات التنفيذ، وتم التوصل إلى معوقات تطبيق التصور المقترح ومنها ارتفاع التكلفة المادية لتطبيق بطاقة الأداء المتوازن، ونقص المعرفة عن بطاقة الأداء المتوازن في قياس الأداء، وعدم توفر الكوادر القادرة على التعامل مع نظام بطاقة الأداء المتوازن، وضعف استخدام التقنيات التكنولوجية الحديثة في الأكاديمية، وضعف الحوافز التشجيعية المقدمة للمعلمين للإقبال على التدريب، وحدد الباحث الضمانات والآليات الواجب توافرها لنجاح التصور المقترح.
The aim of the research is to develop a proposed concept for developing the institutional performance of the professional academy for teachers within the framework of the balanced performance card. The conceptual and intellectual framework of the professional academy for teachers was presented, and the balanced performance card. The researcher used the descriptive approach to his suitability of the research. The researcher applied a questionnaire to the officials of the Professional Academy in the teacher in the governorates of Assiut, Sohag, and Cairo, and the research found that the areas of the balanced performance card represented in education and growth in the professional academy for the teacher, internal operations in the professional academy for the teacher, and the beneficiaries of the professional academy for the teacher, and the financial aspects of The teacher’s professional academy came with an average degree of verification from the point of view of the sample members Which called for the researcher to develop a proposed concept for developing the institutional performance of the professional academy for teachers within the framework of the balanced performance card, and the steps of the executive procedures for the proposed visualization include the following: planning for implementing the balanced performance card, preparing for the application of the balanced performance card, and collecting data on the institution in the professional academy for the teacher, and identifying areas The strategy for applying a card Balanced performance, drawing and developing the main areas of the teacher’s professional academy, identifying critical success factors, preparing the initial report of the card, monitoring and evaluating performance, and each of these steps has a set of implementation mechanisms, and obstacles to applying the proposed vision have been reached, including the high material cost of implementing the performance card Balanced, and the lack of knowledge about the balanced performance card in measuring performance, the lack of cadres able to deal with the balanced performance card system, the weak use of modern technological technologies in the academy, and the weak incentive incentives provided to teachers to attend training, and the researcher identified the guarantees and mechanisms that must be available for the success of the proposed visualization
Keywords: الأداء المؤسسي -- التأهيل التربوي -- التنمية المهنية -- المؤسسات المهنية -- مصر